Influence of acupuncture in treatment of knee osteoarthritis and cartilage repairing - Zhang, Yan (Am J Transl Res, 2016)
As two major non-operative methods, physiotherapy and acupuncture have been proved to be safe and effective in osteoarthritis (OA) treatment. However, only a little study focused on functions of both methods on cartilage repairing. The main goal of this research is to prove and compare effectiveness of acupuncture and physiotherapy on OA, and to explore their possible efficacy on cartilage repairing. One hundred knees of 50 participants with knee osteoarthritis (KOA) were randomly divided into acupuncture group and physiotherapy group. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to evaluate the motor function of knee joints, followed by MRI scanning to measure T2 values in ten cartilage sub-regions in tibiofemoral joints. Significant lower scores of total WOMAC and three subscales on the 4th weekend were observed in both groups than those of the baseline (P < 0.01). For acupuncture group, scores of total WOMAC and three subscales for pain, stiffness and physical function on 4th weekend were significantly lower than those of the physiotherapy group (P < 0.01 and P < 0.05). T2 values in anterior medial tibial sub-region (MTa) and anterior lateral tibial sub-region (LTa) were significantly lower in acupuncture group on 4th weekend than those of the baseline (P < 0.05). No significant difference in T2 values was detected in physiotherapy group. These results indicate that acupuncture represents certain clinical effect on KOA which is superior compared with physiotherapy, and hint the possible roles of acupuncture in promoting cartilage repairing.